The second equation gives you an expression for y that you can substitute into the first equation.

6x - 7(5x+48) = -46

6x - 35x - 336 = -46 (eliminate parentheses)

-29x = 290 (add 336, collect terms)

x = -10 (divide by -29)

5(-10) + 48 = y (use the second equation to find y)

-2 = y

The solution is (x, y) = (-10, -2).

_____

Check

We have used the second equation to get y, so we only need to verify our answer in the first equation.

6(-10) - 7(-2) = -46

-60 + 14 = -46 (yes)

6x - 7(5x+48) = -46

6x - 35x - 336 = -46 (eliminate parentheses)

-29x = 290 (add 336, collect terms)

x = -10 (divide by -29)

5(-10) + 48 = y (use the second equation to find y)

-2 = y

The solution is (x, y) = (-10, -2).

_____

Check

We have used the second equation to get y, so we only need to verify our answer in the first equation.

6(-10) - 7(-2) = -46

-60 + 14 = -46 (yes)